ЖӘМИЙЕТЛИК-СИЯСИЙ ЛЕКСИКАНЫҢ АФФИКСАЦИЯ УСЫЛЫ МЕНЕН ЖАСАЛЫЎЫ - Нажимов, А.Ш. (FAN va JAMIYAT, 2021)
Some derivational affixes in the Karakalpak language are used in the construction of social and political terms. With the help of affixes, terms are generally formed with the following meanings: social and political life; concepts related to people depending on the state of society and their ideological environment. However, the way affixes are applied is different. Some terms are formed with separate affixes. Socio-political words are formed by adding affixes to the words noum, verb and adverb. Not all affixes in a language are used in the same way when constructing socio-political vocabulary. In each lexical-semantic group, affixes are widely used. However, an affix that is effective in forming words using affixes in one lexical-semantic group may not be effective for another lexical-semantic group.